Pewarisan Sifat Ketahanan Tanaman Melon (Cucumis melo L.) terhadap Powdery Mildew (Podosphaera xanthii (Castag.) Braun et Shishkoff) - Budi Setiadi Daryono; Muhammad Taufiq Qurrohman (Universitas Gadjah Mada, 2009)
Powdery mildew is a fungal disease that causes subtantial losses in melon production around the world including Indonesia. Resistant melon cultivar to powdery mildew is important to increase melon production. Hence, the objectives of this study were to study melon resistance against powdery mildew and its inheritance. A F2 population was obtained from self pollination between F1 ♀ 371795 which derived from ♀ PI 371795 X ♂Action 434 and F1 ♀Action 434 which derived from ♀ Action 434 X ♂ PI 371795. In addition, a test cross population was produce by crossing between F1 with Action 434 as a recessive homozygote pa-rent. Furthermore, powdery mildew resistance in a F1, F2 and test cross populations were tested by inoculating powdery mildew which collected from Ngawi regency. The results were evaluated by Chi-square test (χ2). The results showed that a F1, F2 and test cross populations have different resistance levels to powdery mildew. The resistance to powdery mildew in a F2 ♀ PI 371795 population showed segregation and have 3:1 ratio of Mendel inheritance pattern. On the other hand, resistance to powdery mildew in a test cross with PI 371795 as a parent showed segregation with 1:1 ratio. While resistance in a F2 ♀ Action 434 and test cross populations with Action 434 as a parent did not express Mendel inheritance pattern. Based on the result it could be concluded thatn resistance to powdery mildew in PI 371795 as a female parent is controlled by a single dominant gene (pm-I), while resistance to powdery mildew in action 434 as a female parent is suppose to be controlled by several genes (oligogene).